Engineering law - Laidlaw, Robert Everett; Young, C. R. (Clarence Richard), 1879-1964; Dick, Rendall (Heritage, 2018)
Important changes in legislation, and a mounting number of court decisions relevant to the topics here discussed, have made a revision and expansion of the fourth edition necessary. The objective of the book still remains essentially as it was twenty-one years ago, when the first edition appeared. That aim is to present to engineers and engineering students a simple treatment of the legal aspects of engineering undertakings and responsibilities, using a minimum of technical legal terms and avoiding the subtler distinctions and conflicts. As legal problems now arise in a wide range of engineering activities, it has been thought well to add three more chapters. These concern "Mines, Oil and Gas Wells, and Pipe Lines"; "Public Utilities"; and "Public Health."